CRITICAL THINKING SKILLS OF STUDENTS WITH HIGH ACADEMIC ABILITY: PROFILE AND ITS EFFECT ON COGNITIVE LEARNING OUTCOMES - IIN HINDUN; FUAD JAYA MIHARJA; TUTUT INDRIA PERMANA (International Journal of Innovations in Engineering Research and Technology, 2021)
Critical thinking skills (CTS) have been considered as one of the primary competencies of the 21st -Century. The purpose of this correlational research was to map the profile of CTS and examine its relationship to cognitive learning outcomes (CLO) of students with high academic ability. The study was conducted in 2019, involving 35 students from one of the high-quality schools in Malang, Indonesia. Essay tests were used to collect students’ CTS and CLO. The instrument developed by Zubaidah was applied to determine the level of CTS. Applied data analysis was means and simple linear regression. The results showed that the students’ CTS level was categorized as "moderate," and this skill correlated significantly with CLO. Therefore, the empowerment of CTS needs to be optimized to improve student CLO.